Institutional pressures, legitimacy, risks, uncertainty and voluntary adoption of IFRS for SMEs in Vietnam - Hiep Thien, Trinh; Xuan Hung, Nguyen (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The purpose of this study was to determine the impact of institutional variables, risks, and dependence on the voluntary application of international financial reporting standards. The study used a quantitative research method based on regression analysis, with data obtained from a survey from among Vietnam’s small and medium businesses. The findings confirmed that legitimacy, dependence, consistency, time, international trade, uncertainty, operational risk, financial risk, and industry all have a positive impact on the ability to voluntary application international financial reporting standards, with the exception of flexibility, which has a negative impact. The findings of the study have consequences for stakeholders in making proper policy decisions about the application of the International Financial Reporting Standards.